2017
DOI: 10.3389/fncel.2017.00177
|View full text |Cite|
|
Sign up to set email alerts
|

Frontal Connectivity in EEG Gamma (30–45 Hz) Respond to Spinal Cord Stimulation in Minimally Conscious State Patients

Abstract: Spinal cord stimulation (SCS) has become a valuable brain-intervention technique used to rehabilitate patients with disorders of consciousness (DOC). To explore how the SCS affects the cerebral cortex and what possible electrophysiological mechanism of SCS effects on the cortex, the present study investigated the functional connectivity and network properties during SCS in minimally conscious state (MCS) patients. MCS patients received both SCS and sham sessions. Functional connectivity of the phase lock value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
19
2
1
Order By: Relevance
“…Assessing brain responses during spinal cord stimulation in patients in a minimally conscious state has previously been achieved using EEG. Previous studies have shown significantly altered relative power and synchronization in the delta (1–4 Hz) and gamma (30–45 Hz) bands in the frontal areas following spinal cord stimulation ( 173 ), with gamma activity in the frontal cortex causing transient global effects (widespread connectivity and network alterations) and long-lasting local effects (local connectivity alternations that persist beyond stimulation) ( 174 ). The drawback with EEG, however, is that brain responses during spinal cord stimulation cannot be measured in real-time due to interference from the stimulator’s electrical field.…”
Section: From Communication To Advances In Rehabilitationmentioning
confidence: 99%
“…Assessing brain responses during spinal cord stimulation in patients in a minimally conscious state has previously been achieved using EEG. Previous studies have shown significantly altered relative power and synchronization in the delta (1–4 Hz) and gamma (30–45 Hz) bands in the frontal areas following spinal cord stimulation ( 173 ), with gamma activity in the frontal cortex causing transient global effects (widespread connectivity and network alterations) and long-lasting local effects (local connectivity alternations that persist beyond stimulation) ( 174 ). The drawback with EEG, however, is that brain responses during spinal cord stimulation cannot be measured in real-time due to interference from the stimulator’s electrical field.…”
Section: From Communication To Advances In Rehabilitationmentioning
confidence: 99%
“…High-frequency gamma activity has long been associated with cognition and attention [8,9] but has also been shown to encode ongoing pain [10,11]. Moreover, surgically implanted devices such as spinal cord stimulation have shown the potential to modulate cortical gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) activity [12], supporting the hypothesis of supraspinal mechanisms of action for spinal, and potentially peripheral, neuromodulation.…”
Section: Introductionmentioning
confidence: 92%
“…Notably, a series of studies has recorded EEG data synchronously with both non-invasive brain stimulation (TMS [ 89 ], tDCS [ 90 ], and tACS [ 76 ]) and invasive brain stimulation (DBS [ 91 ] and SCS [ 92 , 93 ]). In particular, TMS-EEG stimulates a specific brain area with a single TMS pulse, and monitors the local cortical reactivity as well as the rapid causal interactions among multiple groups of neurons thereafter [ 94 , 95 ].…”
Section: Functional Brain Networkmentioning
confidence: 99%